Developing the OpenFlexure Microscope towards medical use: technical and social challenges of developing globally accessible hardware for healthcare - Knapper, Joe; Whiteford, Freya; Rosen, Daniel; Wadsworth, William; Stirling, Julian; Mkindi, Catherine; Mduda, Joram; Sanga, Valerian L; Nyakyi, Paul T; Mboa Nkoudou, Thomas Hervé; Jafsia, Elisée; Fadanka, Stephane; et al. (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2024)
The OpenFlexure Microscope is an accessible, three-dimensional-printed robotic microscope, with sufficient image quality to resolve diagnostic features including parasites and cancerous cells. As access to lab-grade microscopes is a major challenge in global healthcare, the OpenFlexure Microscope has been developed to be manufactured, maintained and used in remote environments, supporting point-of-care diagnosis. The steps taken in transforming the hardware and software from an academic prototype towards an accepted medical device include addressing technical and social challenges, and are key for any innovation targeting improved effectiveness in low-resource healthcare. This article is part of the Theo Murphy meeting issue 'Open, reproducible hardware for microscopy'.